Lung fluid balance in lambs before and after premature birth. - Bland, R D (1989)
The purpose of this study was to see if lung vascular protein permeability is greater in preterm lambs with respiratory distress than it is in lambs without lung disease. We measured pulmonary vascular pressures, lung lymph flow, and concentrations of protein in lymph and plasma of 10 chronically catheterized preterm lambs (gestation 133 +/- 1 d) for 2-4 h before and for 4-8 h after delivery by cesarean section. All lambs were treated with mechanical ventilation after birth and received a constant intravenous infusion of glucose-saline solution at an hourly rate of 10 ml/kg. Respiratory failure developed in six lambs, in which there was a sustained threefold postnatal increase in lung lymph flow and lymph protein flow, with an even greater increase in pleural liquid drainage. Concentrations of protein in lymph and pleural liquid were almost identical, averaging approximately 75% of the plasma protein concentration. In the four preterm lambs without lung disease, lymph flow and lymph protein flow were either near or below fetal values by 6-8 h after birth, and there was little or no pleural liquid drainage. Extravascular lung water averaged 7.3 +/- .8 g/g dry lung in lambs with respiratory failure compared to 4.8 +/- .5 g/g dry lung in lambs without lung disease. Thus, pulmonary edema with abnormal leakage of protein-rich liquid from the lung microcirculation into the interstitium is an important pathological feature of the respiratory disease that often occurs after premature birth.